2012
DOI: 10.1007/s00253-012-4485-2
|View full text |Cite
|
Sign up to set email alerts
|

Significantly enhanced production of isoprene by ordered coexpression of genes dxs, dxr, and idi in Escherichia coli

Abstract: We constructed a biosynthetic pathway of isoprene production in Escherichia coli by introducing isoprene synthase (ispS) from Populus alba. 1-deoxy-D-xylulose 5-phosphate synthase (dxs), 1-deoxy-D-xylulose 5-phosphate reductoisomerase (dxr) and isopentenyl diphosphate (IPP) isomerase (idi) were overexpressed to enhance the isoprene production. The isoprene production was improved 0.65, 0.16, and 1.22 fold over the recombinant BL21 (pET-30a-ispS), respectively, and idi was found to be a key regulating point for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 27 publications
2
61
1
Order By: Relevance
“…Our result showed that those E. coli strains expressing ls-gpps or ls-Ecgpps produced larger amounts of limonene than the strains expressing gpps-ls or Ecgpps-ls. This result disputes the current notion that the order of the limiting genes in polycistronic operons should correspond to that of terpenoid metabolic pathway in the natural and fine regulation mechanism of microorganisms [19]. In addition, the expression strength of vectors used for limonene biosynthesis was also indicated to be a very important determinant for the final limonene yield.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Our result showed that those E. coli strains expressing ls-gpps or ls-Ecgpps produced larger amounts of limonene than the strains expressing gpps-ls or Ecgpps-ls. This result disputes the current notion that the order of the limiting genes in polycistronic operons should correspond to that of terpenoid metabolic pathway in the natural and fine regulation mechanism of microorganisms [19]. In addition, the expression strength of vectors used for limonene biosynthesis was also indicated to be a very important determinant for the final limonene yield.…”
Section: Discussioncontrasting
confidence: 53%
“…Although overexpression of rate-limiting enzymes in the MEP pathway has been used to produce many terpenoids including isoprene, taxol precursor and levopimaradiene [14][15][16][17][18][19], this method has not been used in the most common engineered strain Escherichia coli to produce limonene. In a previous study, an engineered Escherichia coli, harboring a heterologous GPPS gene from Abies grandis and a LS gene from Mentha spicata, was reported to produce limonene in a titer of merely 5 mg/L (24 h) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Escherichia coli is the most widely used platform organism not only for the production of a wide range of important high-value compounds, such as taxol precursor [1], isoprene [2,3], terpenoids [4], 5-Aminolevulinic acid [5], coenzyme Q 10 [6] and plant-specific phenylpropanoids [7], but also for the solution of global energy-related issues such as biofuel production and biomass conversion [8,9]. In these studies, the construction of synthetic pathway frequently involves the expression of multiple genes.…”
Section: Introductionmentioning
confidence: 99%
“…34°C), its collection from plants is difficult [7]. Hence, much attention and effort have been directed toward isoprene production through metabolically engineered microorganisms [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although these two pathways begin with different precursors, both culminate with the production of two universal 5-carbon isoprenoid precursors, isopentenyl pyrophosphate (IPP) and dimethylallyl pyrophosphate (DMAPP) [10], [11]. The DMAPP can be converted to isoprene by isoprene synthases (IspS), which are cloned from plants and heterologously expressed in microbial hosts [8], [9].…”
Section: Introductionmentioning
confidence: 99%